2013
DOI: 10.1002/adma.201300552
|View full text |Cite
|
Sign up to set email alerts
|

Macrostructuring of Emulsion‐templated Porous Polymers by 3D Laser Patterning

Abstract: Micro-stereolithography (μSL) is used to produce 3D porous polymer structures by templating high internal phase emulsions. A variety of structures are produced, including lines, squares, grids, and tubes. The porosity matches that of materials produced by conventional photopolymerization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
76
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 25 publications
0
76
0
Order By: Relevance
“…A 405 nm microstereolithography setup was used to fabricate threedimensional structures, comprising of the following components: a Digital Micromirror Device (DMD) (Texas Instruments Incorporated, TX, USA), 100 mW 405 nm tunable laser source and associated proprietary software (Vortran Laser Technology Inc, Sacramento, CA, USA), motorised z-axis translation stage apparatus and attached metal stage (Thorlabs Ltd, Cambridgeshire, UK), controlled via proprietary software for the z-stage (APT Software, Thorlabs Ltd, Cambridgeshire, UK), as described previously [23]. The process and experimental setup is illustrated in Fig.…”
Section: Three Dimensional Sample Preparation Using 405 Nm Microsterementioning
confidence: 99%
“…A 405 nm microstereolithography setup was used to fabricate threedimensional structures, comprising of the following components: a Digital Micromirror Device (DMD) (Texas Instruments Incorporated, TX, USA), 100 mW 405 nm tunable laser source and associated proprietary software (Vortran Laser Technology Inc, Sacramento, CA, USA), motorised z-axis translation stage apparatus and attached metal stage (Thorlabs Ltd, Cambridgeshire, UK), controlled via proprietary software for the z-stage (APT Software, Thorlabs Ltd, Cambridgeshire, UK), as described previously [23]. The process and experimental setup is illustrated in Fig.…”
Section: Three Dimensional Sample Preparation Using 405 Nm Microsterementioning
confidence: 99%
“…[18][19][20][21] Therefore, much attention has been focused on the Pickering-HIPEs, which are stabilized by colloidal particles instead of traditional surfactants. [22][23][24][25][26] Not only is less emulsier dose required for emulsions, but also Pickering emulsion droplets exhibit better stabilization against coalescence.…”
Section: Introductionmentioning
confidence: 99%
“…Photoinitiated polymerisation reduces the cure time to seconds, which means that less stable emulsions can be cured which might otherwise destabilise during the long process of thermal curing or with increase in temperature [2,4,10,12] . This approach has potentially increased the versatility of PolyHIPE systems, and there is a growing interest in the use of photocurable monomers for their production [4,8,[11][12][13][14][15][16] . PolyHIPEs have been commercialised for use as 3D environments for cell culture including the development of more complex tissue models.…”
Section: Introductionmentioning
confidence: 99%
“…The use of a sacrificial scaffold has also been used in conjunction with electrospinning to produce microporous electrospun mats with internal channels to introduce a prototype vascular network in these scaffolds [22,23] . Recent studies reported on the use of layer-by-layer stereolithography for selectively photocuring Poly-HIPE emulsions to fabricate customised structures with both random microporosity and controlled macroporosity [11,13,24] . In this process, the templated emulsion is used as the resin for the direct write process.…”
Section: Introductionmentioning
confidence: 99%